Bibliography: terrorism by Region – Southeast Asia - Tinnes, Judith (Perspectives on terrorism, 2021)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on terrorism affecting Southeast Asia. It covers both terrorist activity within the region’s territory (regardless of the perpetrators’ nationality) and terrorist acts by nationals from this region abroad. The bibliography focuses on recent publications (up to January 2021) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. In addition, full-text and reference retrieval systems have been employed to broaden the search.